CIVIL-MILITARY RELATIONS IN PAKISTAN: 1988 TO 2008 - Dr. Saima Butt (International Journal of Contemporary Issues in Social Sciences, 2024)
Since Pakistan’s establishment, civilian governments and military command have worked closely together as a result of modest begging. To meet the needs of Pakistan’s newly formed state government, the military had to be a well-organised institution. There will be no looking back in the barracks for the troops from that day forward. Pakistan has faced persistent security threats since its creation, resulting in large military involvement. The goal of a recent study is to look into the settings and environments in which this cooperation works, as well as the conditions under which it fails. To complete this research, primary and secondary data were employed in conjunction with historical and descriptive research.